Tick ecological studies at Did Tuyura ranch on Boran cattle in Ethiopia - Gebre, S. (EVA, 1994)
Tick populations were observed for a period of 12 months, from October 1991 to September 1992 at monthly intervals on ten Boran (Bos indicus) heifers found at Did Tuyura Ranch in Ethiopia. Four Genera and 12 different tick species were identified from a total of 32052 ticks collected. Of all the ticks collected Rhipicephalus constituted 84.7%; Amblyoma 9.8%; Boophilus 4.8% and Hyaloma 0.4%. The four major tick species recorded in decreasing order of abundance were Rhiphicephalus pulchellus (82.39%); Amblyomma variegatum (7.4%); Boophilus decoloratus (4.7%) and Amblyomma gemma (2.46%). The relative abundance of adult and standard size ticks of these species, their predilection feeding sites, sex ratio and seasonal fluctuations in numbers are discussed in relation to control measures. Anaplasmosis, Babesiosis and Theileriosis (T.mutans) were confined parasitologicaly (Blood smears) and serologically (ELISA) in the ranch with seroprevalence rate of 94.68%, 77.19% and 30.9% for anplasmosis, babisiosis and theiriolosis respectively. The packed cell volume (PCV) value was monitored monthly during all the study period. The result of the study indicated that, although dramatic decrease of PCV was observed during dry season of the year, generally PCV value was within normal range.